Evaluating the Effect of Orthodontic Treatment on Periodontal Health in Patients with Preexisting Periodontal Conditions - Mohammad K. Alam; Mohammad Y. Hajeer; Taif Alsaleh; Balqees Alhadi; Afrah Alsaleh; Raghad Alnsairy; Shahad Alruwaili (Journal of Pharmacy and Bioallied Sciences)
Background: In many cases, orthodontic treatment is necessary to improve the alignment and functionality of teeth. But there is still uncertainty about how orthodontic equipment may affect periodontal health, especially in individuals who already have periodontal disease. Materials and Methods: For this investigation, a total of 50 patients with prior periodontal diseases were chosen. The participants were split into two groups: Group B (n = 25) was the control group and did not get any orthodontic intervention, whereas Group A (n = 25) had orthodontic therapy utilizing fixed appliances. At baseline, six months, and twelve months, periodontal health was evaluated using the Plaque Index (PI), Gingival Index (GI), and Clinical Attachment Level (CAL). Paired t-tests and ANOVA were used to assess the significance of time-series changes in the data. Results: There was a statistically significant increase in plaque accumulation in Group A, as evidenced by the mean PI increasing from 1.2 ± 0.4 at baseline to 1.5 ± 0.5 at 12 months (P < 0.05). Additionally, there was a noteworthy rise in the GI, from 1.1 ± 0.3 to 1.4 ± 0.4 (P < 0.05). Though there was a modest drop in the CAL from 3.5 ± 0.8 mm to 3.4 ± 0.7 mm, it was not statistically significant (P > 0.05) and remained very steady. Group B, on the other hand, showed no appreciable variations in PI, GI, or CAL during the course of the investigation. Conclusion: Patients receiving orthodontic treatment who already have periodontal disease tend to be more prone to plaque buildup and gingival irritation. Nonetheless, the clinical attachment levels can be sustained for the duration of the treatment with proper periodontal maintenance.